FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK DENGAN PERTUMBUHAN KREDIT SEBAGAI VARIABEL INTERVENING (Studi pada Bank Umum Go Public yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Adistya, Renna; Mawardi, Wisnu (Faculty of Economics and Business Diponegoro University, 2018)
This study aims to analyze the factors that effect bank profitability (ROA) in commercial banks go public that is listed on the Indonesia tock Exchange period of 2012-2016. Independent variables used in study are Capital Adequacy Ratio (CAR), Third Party Fund (DPK), Non Performing Loan (NPL) and credit growth as an intervening variable.The population used in this study are all commercial banks go public which is listed on Indonesia Stock Exchange (IDX) period of 2012-2016. Sampling in this study using saturation sampling which resulted in a sample into 43 commercial banks go public. The analysis technique used is Path Analyst which is a development of multiple regression analysis.The results of this study showed that CAR has a positive effect and insignificant to credit growth, DPK has positive effect and significant to credi growth. NPL has negative effect and significant to credit growth. CAR has positive effect and insignificant to profitability. DPK and credit growth have positive and significant to profitability. NPL has negative and significant to profitability. Then, credit growth is able to mediate the effect of DPK to profitability. But credit growth is not able to mediate the effect ofÂ CAR and NPL to profitability.